She got game: Investigating how reputation can be leveraged to improve recruiting effectiveness in National Collegiate Athletic Association women`s basketball - Magnusen, M. J.; Kim, J. W.; McAllister, C. P.; Perrewé, P. L.; Ferris, G. R. (International Journal of Sports Science & Coaching, 2018)
Although recruiting processes and outcomes in National Collegiate Athletic Association sports is an incredibly important facet of collegiate athletics, it is underdeveloped in several areas. Gaps in knowledge exist when it comes to better understanding actual recruits obtained, the role of reputation, and what factors may influence the school-choice decision of elite, female student-athletes. Probit analyses examining data from 500 National Collegiate Athletic Association Division I female basketball players, approximately 100 universities, and 20 National Collegiate Athletic Association conferences yield that recruits` decisions are primarily influenced by the total number of Elite 8 teams and national championships from a team`s affiliated conference, geographic distance between recruits` hometowns and the university, average arena attendance, and the percentage comparing the basketball arena capacity and game attendance. The results make both theoretical and practical contributions by demonstrating the predictive power of reputation, while also offering recruiters actionable information that potential recruits likely are considering each recruiting cycle.